Enhanced Productivity and Fish Abundance at a Submarine Spring in a Coastal Lagoon on Tahiti, French Polynesia - Starke, Claudia; Ekau, Werner; Moosdorf, Nils (Frontiers in Marine Science, 2020)
Submarine groundwater discharge (SGD), the direct discharge of groundwater into the sea, is widely spread. Fresh SGD can occur as focused flow in submarine springs. However, little is known on the impact of submarine springs on marine organisms. For a better understanding of the interaction between SGD and its surrounding organisms, the impact of SGD on the abundance of fish was investigated in a coastal lagoon of Tahiti, French Polynesia. The study is based on the assumption of an enhanced biological production due to increased amounts of nutrient input caused by terrestrial groundwater supply into the sea. Biofouling processes and zooplankton samples were used as indicators for elevated nutrient input due to submarine spring. The main objective was to investigate the effect on the abundance of fish assuming a higher fish abundance possibly caused by a bottom-up control. Presented data show a significantly higher fish abundance around a submarine spring as well as significantly larger growth of algal turfs exposed to groundwater discharge. Zooplankton evaluations suggest slightly higher abundances around the submarine spring. The results suggest elevated nutrient concentrations transmitted by submarine springs may cause a bottom-up control resulting in a higher abundance of fish around the springs at the study site.